Anmeldelse af Historical Dictionaries and Historical Dictionary Resarch (...) - Lundbladh, Carl-Erik (LexicoNordica, 2005)
Anmeldt værk: Historical Dictionaries and Historical Dictionary Research. Papers from the International Conference on Historical Lexicography and Lexicology, at the University of Leicester, 2002. Edited by Julie Coleman and Anne McDermott. Lexicographica Series Maior 123. Tübingen: Max Niemeyer Verlag 2004.